Upper bound for the crossing number of Qn×K3 - Aroonwan Suebsriwichai (2018)
© 2017 by the Mathematical Association of Thailand. All rights reserved. In this paper, we describe a method of finding the upper bound for the crossing Number of Qn×K3. We construct a drawing of Qn× K3, called a 3−axes drawing of Qn×K3. A 3 −axes drawing of Qn×K3is a representation of Qn× K3on the plane such that its vertices are placed on 3 straight lines Liwhere i = 1, 2, 3 with a fixed vertex ordering.